L’université toulousaine et l’outre-mer (1808-1945) - Caroline Barrera (Les Cahiers de Framespa)
This article aims at analyzing how Toulouse University took up the issue of France’s overseas territories from nineteenth century until 1945. As a major educational centre, we could think that overseas relationships were as dynamic as those with many foreign countries. This assumption seems probable because from the 1880’s, the development of the university is concomitant with colonization. Moreover, in several university towns, including Bordeaux, a higher specific colonial training is developed. This analysis is carried out through the prism of professors and students, who are different actors with regard to colonization, even opposing.